Laser transformation hardening of tool steel specimens - Yang, Lin Jiang (2008)
The effects of speed nozzle gap, power input, overlapping runs and pre-hardening on laser transformation hardened ASSAB DF-2 tool steel specimens (equivalent to AISI01) and their wear resistance were studied.